Synthesis and Screening of New [1,3,4]Oxadiazole, [1,2,4]Triazole, and [1,2,4]Triazolo[4,3-b][1,2,4]triazole Derivatives as Potential Antitumor Agents on the Colon Carcinoma Cell Line (HCT-116) - Abdelrehim, El-sayed M. (ACS Omega, 2021)
[Image: see text] New derivatives of [1,3,4]oxadiazole-2-thione and triazole-3-thione were synthesized through the cyclocondensation of dicarbonyl ester 2 with phenyl hydrazine followed by hydrazinolysis to give the corresponding hydrazide, which reacted with carbon disulfide or ammonium thiocyanate to afford [1,3,4]oxadiazole 5 or triazole-3-thione 7, respectively. Hydrazinolysis of compound 5 gave [1,2,4]triazole-3-thiol 9 which was treated with different aromatic aldehydes to obtain 10a–c. Mannich bases 11a–c were obtained from the reaction of Schiff bases 10a–c with morpholine and formaldehyde. Moreover, treatment of triazole-3-thione 7 with hydrazine was followed by cyclocondensation with diethyl oxalate, chloroacetic acid, or formic acid to give the corresponding [1,2,4]triazine-3,4-dione 14, [1,2,4]triazin-4-one 15, or [1,2,4]triazolo[4,3-b][1,2,4] triazole 16, respectively. Screening of some chosen synthesized compounds against the human colon carcinoma cancer cell lines showed that the compound [1,2,4]triazole-3-thiol 9 exhibiting cytotoxic activity was roughly equivalent to standard Vinblastine, while compounds 4, 7, 10, 11a, 14, and 16 exhibited moderate cytotoxic activity.